THE POLICIES OF RECEPTION OF VICTIMS OF DOMESTIC VIOLENCE IN SENADOR CANEDO/GO (CIPEEX, 2025)
The present study arose from the interest in deepening knowledge about domestic violence against women and understanding how the municipality of Senador Canedo has prepared itself to prevent and assist women who go through such a moment. The objective was to understand, through a qualitative approach and deductive method, how women in situations of violence live with public service and with this adversity, strategies in coping and considering the support required and obtained in the public environment. This is a qualitative study, presenting real data on the municipality's actions in dealing with this delicate situation, based on the Maria da Penha Law. The search for help happens in the social environment itself, with family and friends and only after this search do people turn to health and judicial services. It was seen that the municipality of Senador Canedo has a basis for coping but that much needs to be improved and introduced based on what the government provides to all municipalities. To this end, new service strategies must be designed, seeking not only to serve but also to support women who are victims of violence and also encourage those who suffer from it daily and do not have the courage to report it.
Keywords: violence; victims